Kandungan Gizi Pada Kopi Biji Salak (Salacca zalacca) UD Halwa Indoraya Desa Kedungrejo yang Berpotensi Sebagai Produk Pangan Lokal Berantioksi dan Berdaya Saing - m. nasirudin nasir (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
Abstract - During the main harvest, salak becomes very cheap, so it doesn't have a good impact on farmers. To overcome this, farmers must process the fruit into products such as dodol, sweets, chips, sweets, and extracts. This processing produces seeds that have not been utilized. This research aims to process salak seeds into coffee and analyze their contents, potentially food and health products such as antioxidants, caffeine, and proximate analysis. This research is a descriptive study that examines the making of coffee salak seeds and their contents. Making and taking samples was done at the Salak Abian Farmers Group, Sibetan Village, Karangasem. Sample preparation was carried out at the Denpasar Health Polytechnic Health Analysis Section. The sample analysis testing process was carried out at the Laboratory Services Unit, Faculty of Agricultural Technology, Udayana University. The data was analyzed descriptively by presenting tables and narratives of the results obtained regarding product potential. The technological development of salak coffee as a local food product is the processing of the seeds into powder, which is roasted to become coffee. The method of making it is straightforward, almost the same as processing coffee. The content of antioxidant chemicals, caffeine, and proximate analysis can potentially become a local food product typical of Karangase that is globally competitive. This is supported by the antioxidant capacity content of 436.91 mg/L and IC50% 9.37 mg/mL, low caffeine 0.207%, low fat 2.95%, and carbohydrates 80.98%. It is also supported by 6.24% water, 3.49% ash, and 6.34% protein.